TUTELA JURISDICIONAL DO DIREITO À SAÚDE NO ÂMBITO DO SUS NO ESTADO DO MARANHÃO: uma análise da judicialização da saúde no Estado do Maranhão nos anos de 2009 e 2010 - Sousa, Arnaldo Vieira (2013)
The judicialization of health has gradually entered on the agenda of the three Powers of the Republic. The discussion has as a background not only the limits and possibilities of realization of the Brazilian Constitution, but also of our own policy. This study aims to analyze how was the judicialization of health under the Health System in the state of Maranhão in the years 2009 and 2010, in order to assist in the rationalization of discussion. For this, makes use of the historic of progressive immersion of the social issue in Western policy, and then working in the context in which the judicialization of health gained space on the staff of the Brazilian public agenda. Then works with the formation of the right to health as a fundamental right and the social formation of the Brazilian Judiciary, for, shortly after, making a survey of the main criticisms of the judicialization of health regarded as excessive and its comparison to reality in Maranhão in the years of 2009 and 2010.